2016
DOI: 10.1306/08101514152
|View full text |Cite
|
Sign up to set email alerts
|

Regional petroleum alteration trends in Barents Sea oils and condensates as a clue to migration regimes and processes

Abstract: This thesis has been submitted to the Department of Geoscience at the University of Oslo in accordance with requirements for dissertation for the degree of Philosophiae Doctor. The work that forms the basis for this Ph.D. thesis was conducted under the supervision of Prof. Dr. Dag Arild Karlsen and financed by NORECO ASA. Although first drillings were conducted during the early 1980ies, the Barents Sea is still considered a frontier area for petroleum exploration. Despite extensive research on the geologic evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 114 publications
(242 reference statements)
3
28
0
Order By: Relevance
“…7), suggest that this condensate was generated in the late oil window ca. 1.2 -1.8%R c , consistent with a maturity appraisal based on light (C 4 -C 8 ) hydrocarbons (Lerch et al, 2016). Since these data are consistent, this sample is suggested to represent a single charge with no mixing.…”
Section: Variations In Maturation Parameters As Indications Of Mixingsupporting
confidence: 81%
See 4 more Smart Citations
“…7), suggest that this condensate was generated in the late oil window ca. 1.2 -1.8%R c , consistent with a maturity appraisal based on light (C 4 -C 8 ) hydrocarbons (Lerch et al, 2016). Since these data are consistent, this sample is suggested to represent a single charge with no mixing.…”
Section: Variations In Maturation Parameters As Indications Of Mixingsupporting
confidence: 81%
“…Lerch et al (2016) reported that elevated Pr/n-C 17 and slightly higher Ph/n-C 18 values, together with elevated amounts of light hydrocarbons in sample B2 (well 7120/1-2), represent a mixture of a partiallybiodegraded palaeo-oil and a more recent undegraded charge. Slightly increased Pr/n-C 17 and Ph/n-C 18 values are also shown for samples D (well 7120/2-2) and Å (well 7220/6-1), Loppa High; sample X (well 7125/1-1, Måsøy/Nysleppen Fault Complex); and sample Ø (well 7222/6-1 S, Bjarmeland Platform), indicating incipient biodegradation (Fig.…”
Section: Discussion Biodegradationmentioning
confidence: 98%
See 3 more Smart Citations